Intensive Family Intervention as Support for Professional Treatment: Evolution of Symptoms in a Diagnosed Case of Autism Spectrum Disorder - José María Salgado-Cacho; María del Pilar Moreno-Jiménez; María Luisa Ríos-Rodríguez (MDPI AG, 2022)
This article shows the progress achieved in a child who has received professional treatment combined with a family intervention at home. It discusses a 22-month-old patient identified as showing warning signs of autism spectrum disorder (ASD), a diagnosis that was subsequently confirmed through a standardized ADOS-2 test at 31 months of age. To establish the initial working objectives, a functional diagnosis was carried out at 23 months of age using the Battelle Developmental Inventory; a maturational delay was detected, situating the child at an age equivalent to 16 months. A professional intervention was designed in an early childhood care center, complemented by family intervention, so that the hours in which the child participated in learning experiences were increased. Notable advances were made in the areas of cognitive and motor skills, with more standard scores than when initially evaluated. Progress was also observed (though to a lesser extent) in other developmental areas such as language total, adaptive behavior, and self-help, while slight delays in the areas of socio-emotional development and reasoning and academic skills were found.